1996
DOI: 10.1079/bjn19960110
|View full text |Cite
|
Sign up to set email alerts
|

Lysine utilization by growing pigs: simultaneous measurement of protein accretion and lysine oxidation

Abstract: Nitrogen retention and lysine oxidation were measured in growing pigs given diets which supplied 0,0-2 or 08 of the lysine requirement, with other amino acids in relative excess. Eight groups of three female littermate pigs were used: one of each group was given each of the three diets. In half the pigs (four groups) N retention was measured at body weights (W) of approximately 25,35 and 45 kg. The other four littermate groups of three pigs were given the same three diets; when they reached 35 kg W they were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Hence, if lysine balance can be achieved at an intake of 29 mg·kg Ϫ1 ·d Ϫ1 , as our study suggests, then the efficiency of utilization of dietary lysine approaches 100% (ie, the intake needed to balance obligatory losses) at that intake. This is also consistent with the data from animal experiments that showed that when lysine is limiting in the diet it is particularly well conserved (20,26,27).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Hence, if lysine balance can be achieved at an intake of 29 mg·kg Ϫ1 ·d Ϫ1 , as our study suggests, then the efficiency of utilization of dietary lysine approaches 100% (ie, the intake needed to balance obligatory losses) at that intake. This is also consistent with the data from animal experiments that showed that when lysine is limiting in the diet it is particularly well conserved (20,26,27).…”
supporting
confidence: 81%
“…Above this physiologic requirement intake, oxidation increases with increased amino acid intake. In growing pigs, lysine oxidation did increase when diets supplied 0, 0.2, and 0.8 of the lysine requirement but even in this case the changes in lysine oxidation amounted to only 0.38 g/d with an 8.8-g change in lysine intake (20). Hence, our findings in healthy adults are consistent with the view that the 2 test lysine intakes studied (low and intermediate) fall in the range approximating a minimum physiologic requirement value and below.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of amino acid deficiency the first adaptation is to reduce the oxidation of the limiting amino acid (Mnilk et al 1996;Moehn et al 2003). Further adaptations might then involve alterations in the relative rates of synthesis or breakdown (or both) of different proteins according to their amino acid composition, such that the accretion of a protein rich in the deficient amino acid might be synthesized more slowly, or broken down faster, to make more of the limiting amino acid available for the accretion of those proteins which contain less of that amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Although this reduction is in accordance with the decreasing amino acid utilization for protein accretion with increasing stage of maturity [6], the efficiency in heavy preruminant calves is extremely low compared with other species. In pigs, for example, gross efficiencies of protein utilization of 60% up to as high as 81% were reported [7][8][9][10]. For a sound comparison of efficiencies, however, different species should be compared at a similar stage of maturity, and marginal efficiencies, rather than gross efficiencies, should be compared.…”
Section: Introductionmentioning
confidence: 99%